Eclipse: An End-to-End Platform for Low-Cost, Hyperlocal Environmental Sensing in Cities - Daepp, Madeleine; Cabral, Alex; Ranganathan, Vaishnavi; Iyer, Vikram; Counts, Scott; Johns, Paul; Roseway, Asta; Catlett, Charlie; Jancke, Gavin; Gehring, Darren; Needham, Chuck; von Veh, Curtis; et al. (2022 International Conference on Information Processing in Sensor Networks (IPSN), 2022)
This paper presents Eclipse, a platform for low-cost urban environmental sensing using solar-powered and cellular-connected devices. Dense sensor networks promise to monitor pollution at fine spatial and temporal resolutions, yet few cities have actually implemented such networks due to high costs and limited accuracy. We address these barriers by developing an end-to-end framework for urban air quality sensing with minimal infrastructure requirements. We designed an unobtrusive device that collects data on fine particulate matter (PM2.5), temperature, relative humidity, and barometric pressure. A modular design further includes four low-cost gas sensors — Ozone (O3), Nitrogen Dioxide (NO2), Sulfur Dioxide (SO2), and Carbon Monoxide (CO) — selected based on local priorities. We deployed 115 devices across Chicago, reliably collecting data for over 90% of expected sensor-hours from July 2 - September 30, 2021.